Risk factors for low back pain amongst adults in Nigeria and South Africa: a systematic review - Matthew Fay; Michelle Black (BMC Musculoskeletal Disorders)
Abstract Background The burden on the individual, society and healthcare providers of low back pain in the western world is well documented. Globalisation and urbanisation, it has been reported, has led to an increase in low back pain in developing countries such as those situated in Sub-Saharan Africa. Low back pain determinants are framed, according to the individual, social and cultural context. The aim of this systematic review was to determine the risk factors of low back pain in Nigeria and South Africa, whose growing and modernising economies operate alongside more traditional labour-intensive practices provide a comparison for modern-day Sub-Saharan Africa. Methods Study eligibility included: etiological studies (whose primary objective is to explore/determine risk factors of lower back pain within the population) to include published literature AND non-published manuscripts and ‘grey literature’ (i.e. conference abstracts, thesis and preprints where applicable), studies exploring MSK pain in general if more than 80% of the sample complained of LBP, studies focussing on Nigerian or South African residents, studies including individuals aged 18 years or over and reports printed in the English language. Risk of bias was determined using the AXIS and CASP critical appraisal tools. Owing to study heterogeneity a stratified synthesis was performed to analyse study data. Results Thirty-nine studies were included. Overall, a total of twenty-two sociodemographic, lifestyle, occupational and psychosocial risk factors were identified. There is good quality evidence of an association between the following risk factors and low back pain: advancing age, female gender, obesity, nature and duration of work, posture, manual handling, perceptions of work, job autonomy and disease conviction. Conclusion This review suggests common risk factors for low back pain exists in Nigerian and South African populations as they do in other countries. Funding No funding was received for this systematic review. Trail registration The protocol for this review was registered on PROSPERO prior to commencement (protocol registration number: CRD 42023378363). Clinical trial number Not applicable.